Gift Exchange and the Separation of Ownership and Control - Sandra Maximiano; Randolph Sloof; Joep Sonnemans (Tinbergen Institute, 2006)
Numerous gift exchange experiments have found a positive relationship between employers' wage offers and workers' effort levels. In (almost) all these experiments the employer both owns and controls the firm. Yet in reality many firms are characterized by the separation of ownership and control. In this paper we explore to what extent this affects the wage-effort relationship observed. We compare the standard bilateral gift exchange game between an owner-manager and a worker with two trilateral ones where the firm is owned by a shareholder and controlled by a manager. The wage-effort relationship we observe is the same in all three situations. Most strikingly, workers still reward higher wages with higher effort levels, even when the manager responsible for choosing the wage does not share in the firm's profits at all. The results of a fourth treatment in which the wage is exogenously given suggest that workers feel reciprocal towards the firm as a whole; both ownership and control are important for the gift exchange relationship.
Keywords: J41; C91; M52; 330; Gift exchange; multi-level hierarchy; reciprocity; experimental economics